Dental Composite Materials for Direct Restorations (Springer International Publishing, 2018)
This book covers both basic scientific and clinically relevant aspects of dental composite materials with a view to meeting the needs of researchers and practitioners. Following an introduction on their development, the composition of contemporary composites is analyzed. A chapter on polymerization explains the setting reactions and light sources available for light-cured composites. The quality of monomer-to-polymer conversion is a key factor for material properties. Polymerization shrinkage along with the associated stress remains among the most challenging issues regarding composite restorations. A new classification of dental composites is proposed to offer more clinically relevant ways of differentiating between commercially available materials. A review of specific types of composites provides an insight into their key issues. The potential biological issues of dental composites are reviewed in chapters on elution of leachable substances and cariogenicity of resin monomers. Clinical sections focus on material placement, finishing procedures, and the esthetics and clinical longevity of composite restorations. Bonding to tooth tissues is addressed in a separate chapter, as is the efficiency of various composite repair methods. The final chapter discusses future perspectives on dental composite materials.